Future of environmental reporting in the Finnish forest industry - Marileena Koskela (Springer, 2025)
Despite decades of environmental reporting, quality problems remain and hinder reporting comparability between companies and reliability among stakeholders. To assess the problem, a Delphi panel on the measuring and reporting of the environmental impacts and aspects of the Finnish forest industry was arranged, of which one round focused on the future of environmental reporting. The aim is to discuss the experts’ views on the future of environmental reporting from the point of view of the content of environmental reporting, reporting and stakeholders, and the schedule of reporting. The probable future of environmental reporting in the forest industry is expected to follow current environmental reporting. However, the reporting the experts consider preferable would improve the development of reporting, especially in relation to transportation, the use of water and the development of a supply-chain view on reporting. In addition, the quality problems of reporting could be solved with the standardisation of reporting in the forest industry and involvement of the external stakeholders in the reporting process.